SISTEM INFORMASI INVENTORY BAHAN BAKU DAN BARANG MENGGUNAKAN METODE FIFO STUDI KASUS SINERGI CO-WORKING - Alfonsius Lefrandy Pradana; Katon Wijana; Budi Sutedjo (Fakultas Teknologi Informasi, 2022)
Sinergi Co-Working a place that is a collaboration of a workspace and cafe, which is located at Jl. Cendrawasih No.32b, Demangan, Yogyakarta. All inventory recording activities at this cafe are still being done manually. Starting from recording the incoming and outgoing raw materials and goods. As a result, the inventory flow is not good enough to cause inventory to become damaged or production failure. Users who can access bookkeeping are many. This also results in frequent errors in recording, reports that are not detailed or lacking and inventory becomes obstructed and accumulation occurs in the warehouse. The research objective was to create an inventory system for raw materials and goods using the First In First Out method to answer and solve problems that occurred. This research makes inventory recording better and more systematic so that the operational flow of materials and goods is always fresh. Using such a system improves the flow of inventory. And a good display will help employees or users increase their knowledge of product knowledge. The inventory system that has been successfully built was tested on 10 respondents with 11% less agreeable results. The system is needed, but it is still considered lacking by respondents. In the inventory flow that will be in the actual field. It could be that the system runs well but in the field, it doesn't, due to employee negligence. Then the biggest result is Agree 49%. The inventory system is correct and appropriate to answer all existing problems.